Efficient BiVO4 Photoanodes by Postsynthetic Treatment: Remarkable Improvements in Photoelectrochemical Performance from Facile Borate Modification. Issue 52 (8th November 2019) - Meng, Qijun; Zhang, Biaobiao; Fan, Lizhou; Liu, Haidong; Valvo, Mario; Edström, Kristina; Cuartero, Maria; de Marco, Roland; Crespo, Gaston A.; Sun, Licheng
Abstract: Water‐splitting photoanodes based on semiconductor materials typically require a dopant in the structure and co‐catalysts on the surface to overcome the problems of charge recombination and high catalytic barrier. Unlike these conventional strategies, a simple treatment is reported that involves soaking a sample of pristine BiVO4 in a borate buffer solution. This modifies the catalytic local environment of BiVO4 by the introduction of a borate moiety at the molecular level. The self‐anchored borate plays the role of a passivator in reducing the surface charge recombination as well as that of a ligand in modifying the catalytic site to facilitate faster water oxidation. The modified BiVO4 photoanode, without typical doping or catalyst modification, achieved a photocurrent density of 3.5 mA cm −2 at 1.23 V and a cathodically shifted onset potential of 250 mV. This work provides an extremely simple method to improve the intrinsic photoelectrochemical performance of BiVO4 photoanodes. Abstract : A BiVO4 photoanode was modified with borate at the molecular level (B‐BiVO4 ) by a simple immersion method, giving rise to increased photocurrent and decreased onset potential for water oxidation, which is comparable to loading a water‐oxidation co‐catalyst. The self‐anchored borate plays the role of passivator in decreasing the surface charge recombination and also a ligand in modifying the catalytic site to facilitate faster water oxidation.